Effects of the Grain Size on Dynamic Capillary Pressure and the Modified Green–Ampt Model for Infiltration - Yi-Zhih Tsai; Yu-Tung Liu; Yung-Li Wang; Liang-Cheng Chang; Shao-Yiu Hsu (Geofluids)
Darcy-scale capillary pressure is traditionally assumed to be constant. By contrast, a considerable gap exists between the measured and equilibrium capillary pressures when the same moisture saturation is considered with a high flow rate, and this gap is called the dynamic effect on the capillary pressure. In this study, downward infiltration experiments of sand columns are performed to measure cumulative infiltration and to calculate the wetting front depth and wetting front velocity in sands with different grain sizes. We estimate the equilibrium capillary pressure head or suction head at the wetting front using both the classical Green–Ampt (GAM) and modified Green–Ampt (MGAM) models. The results show that the performance of MGAM in simulating downward infiltration is superior to that of GAM. Moreover, because GAM neglects the dynamic effect, it systematically underestimates the equilibrium suction head in our experiments. We also find that the model parameters α^ and β of MGAM are affected by the grain size of sands and porosity, and the dynamic effect of the capillary pressure increases with decreasing grain size and increasing porosity.